Calicophoron daubneyi (Paramphistomidae) in deer of the Šumava National Park, Czech Republic - Consequence of prevalent rumen fluke infection in cattle - Rehbein, Steffen; Vymyslická, Pavla Jůnková; Peterka, Tomáš; Strube, Christina; Visser, Martin; Mayr, Sandra; Lackerschmid, Juliane (Veterinary parasitology, regional studies and reports, 2024)
A substantial parallel increase in prevalence and geographical spread of the rumen fluke, Calicophoron daubneyi, in livestock in western and central Europe has been recognized in the recent past. In the course of the examination of rectum feces of 471 red deer (Cervus elaphus) and one sika deer (Cervus nippon) from the Fascioloides magna endemic Šumava National Park in the years 2021 and 2022, rumen fluke eggs were detected in four red deer (0.8%) and the sika deer and identified as eggs of C. daubneyi by molecular analysis. Subsequent examination of rectal fecal samples of 247 beef cattle from 22 herds of 14 farms located in or nearby the national park revealed rumen fluke eggs in 53 samples (21.5%) originating from 16 herds of 11 farms, molecularly identified as C. daubneyi eggs as well. One C. daubneyi egg positive red deer and three C. daubneyi egg positive cattle samples also contained fasciolid eggs, respectively, which were detected in 9.5% or 3.6% of the total samples from red deer or cattle, respectively. Results of this investigation reveal the first finding of C. daubneyi in sika deer worldwide and in red deer in mainland Europe and add to the growing number of reports on C. daubneyi in livestock in Europe. Considering that the ratio of cattle excreting rumen fluke eggs exceeded that of deer substantially, it can reasonably be assumed that the C. daubneyi infections in deer are a consequence of the prevalent infection in cattle, illustrating a pathogen spillover event from livestock into wildlife.
Keywords: Cattle; Calicophoron daubneyi; bachor; Paramphistomatidae; skot; Prevalence; Deer; Parks, Recreational; nemoci skotu; Trematode Infections; Feces; Rumen; Red deer; Wildlife; Česká republika; infekce červy třídy Trematoda; feces; Rumen fluke; vysoká zvěř; Ruminants; zvířata; Czech Republic; prevalence; Sika deer; Cattle Diseases; veřejné parky; Animals; Liver fluke